Cutaneous Rhinosporiodosis in Lower Limb Mimicking Squamous Cell Carcinoma : A Case Report - Rahman, Md Mustafizur; Nahar, Nazmun; Kiron, Shah Alam; Uddin, Md Nashir; Jahan, Mst Nusrat; Oishi, Sawantee Joarder; Bhakta, Tapan; Ray, Moon (Journal of Shaheed Suhrawardy Medical College, 2020)
Background: Rhinosporidiosis is a chronic granulomatous disease caused by Rhinosporidiumseeberi. Though cutaneous lesions in Rhinosporidiosis are rare, they may simulate many common dermatological conditions including malignancy thus posing a diagnostic dilemma. Surgical excision is treatment of choice but dapsone can also be used as an adjunct to surgery. Case Presentation: Here, we are reporting a case where a 45 year old male presented with painless progressive polypoidal growth in the right lower limb for five months with central ulceration. Inguinal lymph nodes were also enlarged. Clinically the lesion appeared to be squamous cell carcinoma. FNAC from inguinal lymph node showed reactive changes and the patient underwent wide local excision of the mass. Histopathological report showed that it was a case of Rhinosporiodosis and the patient was referred to department of dermatology for better management. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 164-166